Morphological and immunophenotypical characterisation of maturation-associated chicken dendritic cells by wild type and recombinant fowlpox virus infections - Yusof, Sakinah (2020)
Fowlpox is a common viral disease caused by fowlpox virus (FWPV) which infects birds. In commercial poultry farming, this is considered as economically important disease as it can result in lower production of egg besides increasing the rate of mortality. Compared to other viral infectious diseases, study on the interaction of chicken bone marrow-derived dendritic cells (chBM-DCs) with FWPV remains limited. Therefore, this study aimed to characterize the response of chBM-DCs upon stimulation of wild type (WT) FP9 stain of FWPV compared to recombinant FWPV carrying H5 gene of avian influenza virus (AIV) by morphology and expression of surface marker approach. It is hypothesized that FWPV are susceptible to chBM-DCs and have the ability to drive the maturation of the immune cell. In this study, DCs were isolated from chicken femur and cultured for 6 days in the presence of recombinant chicken granulocyte-macrophage colony-stimulating factor (GM-CSF) and recombinant chicken interleukine-4 (IL-4). The cultured population showed typical morphology of chBM-DCs with the formation of dendrites, which are the key morphological characteristics that defined as a sign of maturation. The result showed that infected chBM-DCs expressed enhanced levels of CD86 and MHC class II in comparison to unstimulated chBM-DC. This indicates the phenotypically mature of chBM-DCs upon stimulation of WT FWPV and rFWPV/H5. The maturation process happened when immature DCs capture and process antigen which followed by up regulation of MHC class II surface marker and co-stimulatory molecules such as CD40, CD80 and CD86. The study has demonstrated that both WT FWPV and rFWPV/H5 were susceptible towards DCs and capable in inducing maturation of DCs. In fact, it was shown that rFWPV/H5 induced the functional maturation of DCs better as compared to WT FWPV, phenotypically. Hence, the study of mechanism process of FWPV immune response enhancement could significantly improve the development of vaccines and therapeutics field